Biodegradation studies on new glycopolymers derived from oligomeric d-mannose itaconates and 2-hydroxypropyl acrylate. (September 2019) - Pană, Ana-Maria; Gherman, Vasile; Sfȋrloagă, Paula; Rusu, Gerlinde; Bandur, Geza; Popa, Marcel; Rusnac, Lucian-Mircea; Dumitrel, Gabriela-Alina
Abstract: We have synthesized herein new glycopolymers derived from sugar (d -mannose) oligomers with itaconic moiety and 2-hydroxypropyl acrylate in different weight ratios (1:1, 1:2, 1:3 and 1:4), in bulk, using benzoyl peroxide as initiator. These glycopolymers were characterized using FTIR spectroscopy, TG analysis, SEM, while their copolymerization process was studied from kinetics point of view using DSC. Biodegradation studies were performed in the microbiology laboratory using in situ grown cultures, provided by water taken out of Bega River that crosses Timişoara (Romania). The glycopolymer with the greatest sugar content displayed the best biodegradation pattern, losing more than 45% of its weight in just 14 days of incubation in water, at 37 °C. The thermal stability analysis was run again on the biodegraded samples and proved dramatical changes in thermal behavior profile, indicating sugar skeleton altering after a 14 days exposure to microbial environment. FTIR spectroscopy performed before and after biodegradation process revealed important changes in glycopolymer structure suggesting the sugar moiety has been the subject of microbial attack. Highlights: This study presents the biodegradation of glycopolymer samples in water from Bega River, in aerobic conditions at 37 °C. The glycopolymers display good properties as plastic materials and degrade due to natural microbial flora from water. Microorganisms use mostly sugar moiety from polymeric backbone as C source, fact proved by FTIR and TG analyses. New glycopolymers derived fromd -mannose are susceptible to biodegradation in presence of natural bacteria from Bega River.